THE RELATIONSHIP OF GRAVIDA WITH THE INCIDENCE OF PRECLAMPSIA IN PREGNANT WOMEN IN THE DELIVERY of RSIA MUHAMMADIYAH PROBOLINGGO - Rizki Fitrianingtyas (LPPM Universitas dr. Soebandi, 2023)
Preeclampsia is a disorder found during pregnancy with signs such as hypertension, proteinuria, and edema which usually occurs after 20 weeks to 48 hours of gestation. The incidence of pre-eclampsia can be obtained from the history of the pregnant woman's pregnancy. The purpose of this study was to determine whether there is a relationship between gravida and the incidence of preeclampsia in pregnant women in the maternity ward of RSIA Muhammadiyah Probolinggo. The research method used is an analytic correlation study with a cross sectional approach using secondary data through medical records. The samples used were all pregnant women who experienced pre-eclampsia in the period January 1, 2021 – December 31, 2021. The sampling technique used was simple random sampling with a total of 100 pregnant women. Analysis using Spearman rank with SPSS 2.0. The results of this study showed that 47% of primigravida mothers had severe preeclampsia and 15% had mild preeclampsia. While in multi gravida as much as 30% had mild preeclampsia and 8% had severe preeclampsia. The results of the SPSS calculation using Spearman Rank with a sample size of 100, then the value of Sig. (2-tailed) is 0.00 as the basis for the decision above, it can be concluded that there is a significant relationship between Gravida and the incidence of Pre-eclampsia. Then from the output above, it is known that the Correlation Coefficient value is 0.534, so this value indicates a relationship with a moderate correlation between Gravida and the level of Pre-eclampsia. This theory also states that due to a decrease in human antigen G protein (HLA), which plays an important role in modulating the immune response, the mother rejects the products of conception.